Printed wiring board and method for manufacturing the same
By using a photosensitive resin composition containing carboxyl resin and olefinic unsaturated compounds, through-holes with small and large diameter portions are formed, solving the problem of low conductivity reliability of multilayer printed wiring boards and improving conductivity reliability and stability.
Patent Information
- Application Number
- CN202111306408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2021-11-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-11-05
AI Technical Summary
In the prior art, the conductivity reliability of multilayer printed wiring boards is low, especially when stress is generated in the conductor of the circuit, cracks are prone to occur.
A negative photosensitive resin composition containing carboxyl-containing resin, olefinic unsaturated compound and photopolymerization initiator is used to form through-holes in the interlayer insulating layer through exposure and development treatment. The through-holes have special shapes with small and large diameter portions, which improves the conductivity reliability.
It enhances the conductivity reliability of printed wiring boards, reduces the occurrence of interface cracks between the through conductor and the second conductor layer, and improves the stability and reliability of conductive connections.
Smart Images

Figure CN114449745B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to a printed wiring board and a method for producing the printed wiring board, and more particularly to a printed wiring board including an interlayer insulating layer having a through hole and a via conductor, and a method for producing the printed wiring board. Background Art
[0002] In a printed wiring board, a via may be formed in an interlayer insulating layer.
[0003] For example, Patent Document 1 discloses a method for manufacturing a multilayer printed wiring board, including the step of irradiating a plastic film in close contact with the surface of an insulating layer containing 35% by mass or more of an inorganic filler with a carbon dioxide laser to form a blind hole having a top diameter of 100 μm or less.
[0004] Patent Document 1: Japanese Patent Application Publication No. 2016-181731 Summary of the invention
[0005] An object of the present disclosure is to provide a printed wiring board having a via with high conduction reliability and a method for manufacturing the printed wiring board.
[0006] A printed wiring board according to one embodiment of the present disclosure comprises a first conductor layer, a second conductor layer, an interlayer insulating layer sandwiched between the first conductor layer and the second conductor layer, a through hole penetrating the interlayer insulating layer, and a via conductor disposed in the through hole and conducting the first conductor layer with the second conductor layer. The interlayer insulating layer is a cured product of a negative photosensitive resin composition containing a carboxyl resin (A), an unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule, and a photopolymerization initiator (C). The through hole has a first end, a second end, and a small diameter portion, the first end being an end on the first conductor layer side, the second end being an end on the second conductor layer side, and the small diameter portion being located between the first end and the second end and having a diameter smaller than the diameter of the second end.
[0007] A method for manufacturing a printed wiring board according to one embodiment of the present invention is a method for manufacturing the above-mentioned printed wiring board, comprising: preparing the above-mentioned negative photosensitive resin composition and a substrate, wherein the above-mentioned negative photosensitive resin composition contains the above-mentioned carboxyl-containing resin (A), the above-mentioned unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule, and the above-mentioned photopolymerization initiator (C), and the above-mentioned substrate has an insulating layer and the above-mentioned second conductor layer overlapping the above-mentioned insulating layer; overlapping a film made from the above-mentioned photosensitive resin composition on the above-mentioned substrate in a manner covering the above-mentioned second conductor layer; and exposing a negative pattern-shaped area of the above-mentioned film containing the pattern of the above-mentioned through hole, and then performing a development treatment using an alkaline aqueous solution, thereby manufacturing the above-mentioned interlayer insulating layer and the above-mentioned through hole penetrating the above-mentioned interlayer insulating layer.
[0008] According to one aspect of the present disclosure, it is possible to provide a printed wiring board having a via with high conduction reliability and a method for manufacturing the printed wiring board. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1A It is a cross-sectional view showing the process of manufacturing a printed wiring board.
[0010] Figure 1B It is a cross-sectional view showing the process of manufacturing a printed wiring board.
[0011] Figure 1C It is a cross-sectional view showing the process of manufacturing a printed wiring board.
[0012] Figure 1D It is a cross-sectional view showing the process of manufacturing a printed wiring board.
[0013] Figure 1E It is a cross-sectional view showing the process of manufacturing a printed wiring board.
[0014] Explanation of symbols
[0015] 3 Second conductor layer
[0016] 4. Capsule
[0017] 6 Through holes
[0018] 61 First End
[0019] 62 Second End
[0020] 63 Small Trail
[0021] 7 Interlayer insulation layer
[0022] 8 First conductor layer
[0023] 9 Via conductor DETAILED DESCRIPTION
[0024] (1) Details of the topic
[0025] Japanese Patent Publication No. 2016-181731 discloses a method for manufacturing a multilayer printed wiring board, including the following steps: irradiating a carbon dioxide laser from a plastic film that is closely attached to the surface of an insulating layer containing 35% or more of an inorganic filler material by mass to form a blind hole with a top diameter of 100 μm or less. However, according to the inventors, the invention described in Japanese Patent Publication No. 2016-181731 has room for improvement in the conduction reliability of the via. The conduction reliability of a tapered via is easily reduced.
[0026] The inventors have obtained the knowledge that cracks may occur in via conductors of the interlayer insulating layer, which deteriorates conduction reliability, through research and development of materials for the interlayer insulating layer.
[0027] Therefore, the inventors have conducted research and development to provide a printed wiring board having a via with high conduction reliability and a method for producing the printed wiring board, and have completed the present disclosure as a result.
[0028] (2) Summary
[0029] One embodiment of the present disclosure will be described.
[0030] The printed wiring board 11 of the present embodiment includes a first conductor layer 8, a second conductor layer 3, an interlayer insulating layer 7 interposed between the first conductor layer 8 and the second conductor layer 3, a through hole 6 penetrating the interlayer insulating layer 7, and a via conductor 9 disposed in the through hole 6 and electrically connecting the first conductor layer 8 and the second conductor layer 3 (see Figure 1E ). The interlayer insulating layer 7 is a cured product of a negative photosensitive resin composition containing a carboxyl resin (A), an unsaturated compound having at least one ethylenically unsaturated bond in one molecule (B), and a photopolymerization initiator (C). The through hole 6 has a first end 61, a second end 62, and a small diameter portion 63, wherein the first end 61 is an end on the first conductor layer 8 side, the second end 62 is an end on the second conductor layer 3 side, and the small diameter portion 63 is located between the first end 61 and the second end 62 and has a diameter smaller than the diameter of the second end 62.
[0031] In this embodiment, the interlayer insulating layer 7 is made of a negative photosensitive resin composition containing a carboxyl resin (A), an unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule, and a photopolymerization initiator (C). Therefore, the interlayer insulating layer 7 is made by exposing the film 4 made of the photosensitive resin composition in a pattern and then developing it with an alkaline aqueous solution, thereby making it easy to make the through hole 6 having the small diameter portion 63.
[0032] The reason why the small diameter portion 63 is easily formed is presumed to be as follows. By irradiating light to the surface of the first end 61 of the film 4 formed of the negative photosensitive resin composition where the through hole 6 is formed, when the film 4 is exposed, the light is scattered inside the film 4, so that the wider portion is easier to cure as it is closer to the deep part of the film 4. As a result, the non-cured portion 5 that becomes the through hole 6 gradually becomes smaller, and it is easy to form a small diameter portion 63 with a smaller diameter than the first end 61. In addition, at the deeper side inside the film 4, light is absorbed by the film 4, and it is difficult for the light to reach, and the influence of the scattering of light is reduced, so it is not easy to cure the film 4, so the diameter of the second end 62 is larger than the diameter of the small diameter portion 63, and the through hole 6 is easy to become a shape that widens from the small diameter portion 63 to the second end 62.
[0033] It is particularly preferred that the photosensitive resin composition has the following characteristics: when a film 4 having a film thickness of 5 μm to 100 μm is prepared from the photosensitive resin composition, ultraviolet rays having a spectral intensity at at least one wavelength in the wavelength range of 365 nm ± 65 nm are irradiated to the region other than the circular portion having a diameter of 5 μm to 100 μm in the film 4, and then the film 4 is subjected to a development treatment using an alkaline aqueous solution, a through hole 6 is formed in the circular portion, and the through hole 6 has a small diameter portion 63. It is preferred that the diameter of the small diameter portion 63 of the through hole 6 at this time is 65% or more and less than 100% relative to the diameter of the second end 62, the diameter of the first end 61 is 65% or more relative to the diameter of the second end 62, and the diameter of the first end 61 is 100 μm or less. Such characteristics can be achieved within the composition range of the photosensitive resin composition described in detail later. It should be noted that the method of irradiating the film 4 with ultraviolet rays may be an exposure method using a negative mask or a direct drawing method. Examples of specific test methods and conditions are described in the Example column.
[0034] In addition, in the present embodiment, since the through hole 6 has such a shape, even if a load due to heat is applied to the via conductor 9 and stress is generated in the via conductor 9, cracks are unlikely to be generated at the interface between the via conductor 9 and the second conductor layer 3. Therefore, it is easy to obtain good conduction reliability between the first conductor layer 8 and the second conductor layer 3 using the via. It is presumed that this is because in the present embodiment, as described above, the inner surface of the through hole 6 of the interlayer insulating layer 7 has a shape in which the diameter increases from the small diameter portion 63 toward the second end 62, so even if stress is generated in the via conductor 9, the stress is more likely to be concentrated on the small diameter portion 63 than on the second end 62 of the via.
[0035] The minimum diameter of the small diameter portion 63 is preferably 65% or more and less than 100% of the diameter of the second end 62. In this case, the conduction reliability brought about by the passage is particularly easy to obtain. If the minimum diameter of the small diameter portion 63 is 95% or less of the diameter of the second end 62, it is more preferred, and if it is 90% or less, it is further preferred. In addition, if the minimum diameter of the small diameter portion 63 is 67% or more of the diameter of the second end 62, it is more preferred, and if it is 79% or more, it is further preferred.
[0036] The diameter of the first end 61 is preferably 65% or more relative to the diameter of the second end 62. At this time, by immersing the plating solution in the through hole 6, it is easy to make the via conductor 9. That is, it is easy to make the via conductor 9 by the plating method. Therefore, it is easy to obtain further good conduction reliability. From the viewpoint of obtaining good resolution when making the through hole 6, the diameter of the first end 61 is more preferably 70% or more relative to the diameter of the second end 62, more preferably 75% or more, and particularly preferably 80% or more. In addition, the diameter of the first end 61 is preferably less than 130% relative to the diameter of the second end 62, more preferably less than 120%, more preferably less than 110%, and particularly preferably less than 100%.
[0037] The diameter of first end 61 is preferably 100 μm or less. In this case, via conductor 9 can be easily formed in through hole 6 by plating or the like. Therefore, better conduction reliability can be easily obtained. The diameter of first end 61 is, for example, 5 μm or more.
[0038] (3) Photosensitive resin composition
[0039] The photosensitive resin composition of the present embodiment will be described in detail below. It should be noted that in the following description, "(meth)acrylic acid" refers to at least one of "acrylic acid" and "methacrylic acid". For example, (meth)acrylate refers to at least one of acrylate and methacrylate.
[0040] The photosensitive resin composition of the present embodiment contains a carboxyl group-containing resin (A), an unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule, and a photopolymerization initiator (C).
[0041] The carboxyl-containing resin (A) preferably contains a carboxyl-containing resin (A1) having a bisphenol fluorene skeleton represented by the following formula (1). If the carboxyl-containing resin (A) has a bulky bisphenol fluorene skeleton, light scattering is less likely to occur in the deep part when the film 4 made of the photosensitive resin composition is irradiated with ultraviolet rays. In addition, the carboxyl-containing resin (A1) can impart high heat resistance and insulation reliability to the cured product of the photosensitive resin composition by having a bisphenol fluorene skeleton.
[0042]
[0043] In formula (1), R1 to R8 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, or a halogen. That is, R1 to R8 in formula (1) may each be hydrogen, but may also be an alkyl group having 1 to 5 carbon atoms, or a halogen. This is because even if the hydrogen in the aromatic ring is replaced by a low molecular weight alkyl group or a halogen, it will not have an adverse effect on the physical properties of the carboxyl-containing resin (A1). On the contrary, by being replaced, the heat resistance or flame retardancy of the cured product of the photosensitive resin composition containing the carboxyl-containing resin (A1) may be improved.
[0044] The carboxyl group-containing resin (A1) is synthesized by, for example, reacting an epoxy compound (a1) having a bisphenol fluorene skeleton represented by the formula (1) with an unsaturated group-containing carboxylic acid (a2) and reacting the intermediate obtained with an acid anhydride (a3).
[0045] The epoxy compound (a1) has, for example, a structure represented by the following formula (2). In formula (2), n is, for example, an integer in the range of 0 to 20. In order to appropriately control the molecular weight of the carboxyl-containing resin (A1), the average value of n is more preferably in the range of 0 to 1. If the average value of n is in the range of 0 to 1, it is easy to suppress the excessive increase in the molecular weight of the carboxyl-containing resin (A1). In addition, in formula (2), R1 to R8 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, or a halogen.
[0046]
[0047] The unsaturated group-containing carboxylic acid (a2) contains, for example, a compound having only one ethylenically unsaturated group in one molecule. More specifically, the unsaturated group-containing carboxylic acid (a2) contains, for example, at least one compound selected from acrylic acid, methacrylic acid, ω-carboxy-polycaprolactone (n≈2) monoacrylate, crotonic acid, cinnamic acid, 2-acryloyloxyethyl succinic acid, 2-methacryloyloxyethyl succinic acid, 2-acryloyloxyethyl phthalic acid, 2-methacryloyloxyethyl phthalic acid, 2-acryloyloxypropyl phthalic acid, 2-methacryloyloxypropyl phthalic acid, 2-acryloyloxyethyl maleic acid, 2-methacryloyloxyethyl maleic acid, β-carboxyethyl acrylate, 2-acryloyloxyethyl tetrahydrophthalic acid, 2-methacryloyloxyethyl tetrahydrophthalic acid, 2-acryloyloxyethyl hexahydrophthalic acid, and 2-methacryloyloxyethyl hexahydrophthalic acid. It is preferred that the unsaturated group-containing carboxylic acid (a2) contains acrylic acid. In addition, when the unsaturated group-containing carboxylic acid (a2) contains acrylic acid, the acrylic acid preferably contains 50 mol% or more of the unsaturated group-containing carboxylic acid (a2), more preferably 80 mol% or more, further preferably 85 mol% or more, and particularly preferably 90 mol% or more.
[0048] When the epoxy compound (a1) is reacted with the unsaturated group-containing carboxylic acid (a2), an appropriate method can be adopted. For example, the unsaturated group-containing carboxylic acid (a2) is added to the solvent solution of the epoxy compound (a1), and a thermal polymerization inhibitor and a catalyst are further added as needed and stirred and mixed to obtain a reactive solution. The intermediate can be obtained by reacting the reactive solution at a temperature of preferably 60°C to 150°C, more preferably 80°C to 120°C using a conventional method. The solvent at this time may contain, for example, ketones such as methyl ethyl ketone and cyclohexanone, aromatic hydrocarbons such as toluene and xylene, and acetates such as ethyl acetate, butyl acetate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and dialkyl glycol ethers. The thermal polymerization inhibitor may contain, for example, at least one component selected from hydroquinone, methyl hydroquinone and hydroquinone monomethyl ether. The catalyst may contain at least one component selected from, for example, tertiary amines such as benzil dimethylamine and triethylamine, quaternary ammonium salts such as trimethylbenzylammonium chloride and methyltriethylammonium chloride, triphenylphosphine, and triphenylantimony.
[0049] The catalyst particularly preferably contains triphenylphosphine. That is, it is preferred that the epoxy compound (a1) and the unsaturated group-containing carboxylic acid (a2) are reacted in the presence of triphenylphosphine. In this case, the ring-opening addition reaction between the epoxy group in the epoxy compound (a1) and the unsaturated group-containing carboxylic acid (a2) is particularly promoted, and a reaction rate (conversion rate) of 95% or more, or 97% or more, or approximately 100% can be achieved.
[0050] It is also preferred that epoxy compound (a1) and unsaturated group-containing carboxylic acid (a2) are reacted under air bubbling. At this time, the addition polymerization of unsaturated groups can be suppressed, the increase of the molecular weight of the intermediate and the gelation of the solution of the intermediate can be suppressed. In addition, the excessive coloring of the carboxyl-containing resin (A1) as the final product can be suppressed.
[0051] When the epoxy compound (a1) and the unsaturated group-containing carboxylic acid (a2) are reacted, the amount of the unsaturated group-containing carboxylic acid (a2) is preferably 0.8 mol to 1.2 mol per 1 mol of epoxy groups in the epoxy compound (a1). In this case, a photosensitive resin composition having excellent photosensitivity and stability can be obtained.
[0052] The intermediate obtained in this way has a hydroxyl group generated by the reaction between the epoxy group of the epoxy compound (a1) and the carboxyl group of the unsaturated group-containing carboxylic acid (a2).
[0053] Next, the intermediate is reacted with an acid anhydride (a3). The acid anhydride (a3) contains, for example, an acid dianhydride (a4).
[0054] The acid dianhydride (a4) is a compound having two acid anhydride groups. The acid dianhydride (a4) may contain anhydride of tetracarboxylic acid. The acid dianhydride (a4) may contain, for example, at least one compound selected from 1,2,4,5-benzenetetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, methylcyclohexenetetracarboxylic dianhydride, tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, ethylenetetracarboxylic dianhydride, 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride, glycerol bis(trimellitic anhydride ester) monoacetate, ethylene glycol bis(trimellitic anhydride ester), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, 1,2,3,4-butanetetracarboxylic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride. In particular, the acid dianhydride (a4) preferably contains 3,3',4,4'-biphenyltetracarboxylic dianhydride. In this case, good developability of the photosensitive resin composition can be ensured, and the stickiness of the film 4 made of the photosensitive resin composition can be suppressed while improving the insulation reliability and plating resistance of the cured product.
[0055] Acid anhydride (a3) may contain acid monoanhydride (a5). Acid monoanhydride (a5) is a compound having one acid anhydride group. Acid monoanhydride (a5) may contain anhydride of dicarboxylic acid. Acid monoanhydride (a5) may contain, for example, one or more compounds selected from phthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, methylsuccinic anhydride, maleic anhydride, citraconic anhydride, glutaric anhydride, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride and itaconic anhydride. It is particularly preferred that acid monoanhydride (a5) contains 1,2,3,6-tetrahydrophthalic anhydride. That is, it is preferred that acid anhydride (a3) contains 1,2,3,6-tetrahydrophthalic anhydride. In this case, it is possible to ensure good developability of the photosensitive resin composition, and further improve the insulation reliability and plating resistance of the cured product while further suppressing the viscosity of the film 4 formed by the photosensitive resin composition. The content of 1,2,3,6-tetrahydrophthalic anhydride is preferably in the range of 20 mol% to 100 mol%, more preferably in the range of 40 mol% to 100 mol%, relative to the total amount of the acid monoanhydride (a5), but is not limited thereto.
[0056] When reacting the intermediate with the acid anhydride (a3), an appropriate method can be used. For example, by adding the acid anhydride (a3) to the solvent solution of the intermediate, further adding a thermal polymerization inhibitor and a catalyst as needed and stirring and mixing, a reactive solution is obtained. The reactive solution is reacted at a temperature of preferably 60°C to 150°C, particularly preferably 80°C to 120°C using a conventional method to obtain a carboxyl-containing resin (A1) having a bisphenol fluorene skeleton. As solvents, catalysts and polymerization inhibitors, appropriate substances can be used, and the solvents, catalysts and polymerization inhibitors used in the synthesis of the intermediate can also be used directly.
[0057] The catalyst particularly preferably contains triphenylphosphine. That is, it is preferred that the intermediate reacts with the acid anhydride (a3) in the presence of triphenylphosphine. In this case, the reaction between the intermediate and the acid anhydride (a3) is particularly accelerated, and a reaction rate (conversion rate) of 90% or more, 95% or more, 97% or more, or approximately 100% can be achieved.
[0058] When the acid anhydride (a3) contains the acid dianhydride (a4), the amount of the acid dianhydride (a4) is preferably 0.05 mol to 0.24 mol per 1 mol of the epoxy group of the epoxy compound (a1). In this case, a carboxyl group-containing resin (A1) having a bisphenol fluorene skeleton with an appropriately adjusted acid value and molecular weight can be easily obtained.
[0059] When the acid anhydride (a3) further contains an acid monoanhydride (a5), the amount of the acid monoanhydride (a5) is preferably 0.3 mol to 0.7 mol per 1 mol of the epoxy group of the epoxy compound (a1). In this case, a carboxyl-containing resin (A1) having a bisphenol fluorene skeleton with an appropriately adjusted acid value and molecular weight can be easily obtained.
[0060] It is also preferred to react the intermediate with the acid anhydride (a3) under air bubbling. In this case, excessive increase in molecular weight of the produced carboxyl group-containing resin (A1) having a bisphenol fluorene skeleton can be suppressed, thereby particularly improving the developability of the photosensitive resin composition with an alkaline aqueous solution.
[0061] Components other than the carboxyl group-containing resin (A1) having a bisphenol fluorene skeleton in the photosensitive resin composition will be described.
[0062] As described above, the photosensitive resin composition contains the carboxyl group-containing resin (A), the unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule, and the photopolymerization initiator (C).
[0063] The carboxyl-containing resin (A) may contain only the carboxyl-containing resin (A1) having a bisphenol fluorene skeleton, or may contain only the carboxyl-containing resin other than the carboxyl-containing resin (A1) having a bisphenol fluorene skeleton. Alternatively, it may contain both the carboxyl-containing resin (A1) having a bisphenol fluorene skeleton and the carboxyl-containing resin other than the carboxyl-containing resin (A1). The carboxyl-containing resin other than the carboxyl-containing resin (A1) having a bisphenol fluorene skeleton includes a carboxyl-containing resin not having a bisphenol fluorene skeleton (hereinafter also referred to as the carboxyl-containing resin (A2)).
[0064] The carboxyl-containing resin (A2) may contain, for example, a compound having a carboxyl group but not photopolymerizable (hereinafter referred to as component (A2-1)). Component (A2-1) contains, for example, a polymer of an ethylenically unsaturated monomer containing an ethylenically unsaturated compound having a carboxyl group. The ethylenically unsaturated compound having a carboxyl group may contain compounds such as acrylic acid, methacrylic acid, and ω-carboxyl-polycaprolactone (n≈2) monoacrylate. The ethylenically unsaturated compound having a carboxyl group may also contain a reactant of pentaerythritol triacrylate, pentaerythritol trimethacrylate, etc. with a dibasic acid anhydride. The ethylenically unsaturated monomer may further contain ethylenically unsaturated compounds that do not have a carboxyl group, such as 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, a straight-chain or branched aliphatic or alicyclic (wherein the ring may have a portion of unsaturated bonds) (meth)acrylate.
[0065] The carboxyl-containing resin (A2) may contain a compound having a carboxyl group and an ethylenically unsaturated group (hereinafter referred to as component (A2-2)). In addition, the carboxyl-containing resin (A2) may contain only component (A2-2). Component (A2-2) contains, for example, a resin (referred to as the first resin (x)) that is a reactant of an intermediate with at least one compound (x3) selected from polycarboxylic acids and their anhydrides, the intermediate being a reactant of an epoxy compound (x1) having two or more epoxy groups in one molecule and an ethylenically unsaturated compound (x2). The first resin (x) is obtained, for example, by adding compound (x3) to an intermediate, the intermediate being obtained by reacting an epoxy group in the epoxy compound (x1) with a carboxyl group in the ethylenically unsaturated compound (x2). The epoxy compound (x1) may contain appropriate epoxy compounds such as cresol novolac type epoxy compounds, phenol novolac type epoxy compounds, and biphenyl novolac type epoxy compounds. It is particularly preferred that the epoxy compound (x1) contains at least one compound selected from the group consisting of biphenyl novolac epoxy compounds and cresol novolac epoxy compounds. The epoxy compound (x1) may contain only a biphenyl novolac epoxy compound, or may contain only a cresol novolac epoxy compound. At this time, since the main chain of the epoxy compound (x1) contains an aromatic ring, the degree to which the cured product of the photosensitive resin composition is corroded by an oxidizing agent such as potassium permanganate can be significantly reduced. The epoxy compound (x1) may contain a polymer of an ethylenically unsaturated compound (z). The ethylenically unsaturated compound (z) contains a compound (z1) having an epoxy group such as (meth) acrylate glycidyl, or further contains a compound (z2) not having an epoxy group such as 2-(meth) acryloyloxyethyl phthalate. The ethylenically unsaturated compound (x2) preferably contains at least one of acrylic acid and methacrylic acid. The compound (x3) contains, for example, one or more compounds selected from polycarboxylic acids such as phthalic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, and anhydrides of these polycarboxylic acids. Particularly preferably, the compound (x3) contains at least one polycarboxylic acid selected from phthalic acid, tetrahydrophthalic acid, and methyltetrahydrophthalic acid.
[0066] (A2-2) component may contain a resin (referred to as the second resin (y)) as a reactant of a polymer of an ethylenically unsaturated monomer containing an ethylenically unsaturated compound having a carboxyl group and an ethylenically unsaturated compound having an epoxy group. The ethylenically unsaturated monomer may further contain an ethylenically unsaturated compound not having a carboxyl group. The second resin (y) is obtained by reacting an ethylenically unsaturated compound having an epoxy group with a portion of the carboxyl group in the polymer. The ethylenically unsaturated monomer may further contain an ethylenically unsaturated compound not having a carboxyl group. The ethylenically unsaturated compound having a carboxyl group contains compounds such as acrylic acid, methacrylic acid, ω-carboxyl-polycaprolactone (n≈2) monoacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate. The ethylenically unsaturated compound without a carboxyl group includes, for example, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, and compounds such as linear or branched aliphatic or alicyclic (wherein the ring may have a portion of unsaturated bonds) (meth)acrylates. The ethylenically unsaturated compound having an epoxy group preferably includes glycidyl (meth)acrylate.
[0067] The carboxyl-containing resin (A) contains only the carboxyl-containing resin (A1), only contains the carboxyl-containing resin (A2), or contains the carboxyl-containing resin (A1) and the carboxyl-containing resin (A2). The carboxyl-containing resin (A) preferably contains more than 25% by mass of the carboxyl-containing resin (A1), more preferably contains more than 40% by mass, further preferably contains more than 60% by mass, and particularly preferably contains 100% by mass. At this time, the excellent photosensitivity of the photosensitive resin composition and the developability using alkaline aqueous solution can be ensured. In addition, the heat resistance and insulation reliability of the cured product of the photosensitive resin composition can be particularly improved. And then, the viscosity of the film 4 formed by the photosensitive resin composition can be fully reduced.
[0068] The weight average molecular weight of the carboxyl-containing resin (A) is preferably 700 to 100,000. If the weight average molecular weight of the carboxyl-containing resin (A) is 700 or more, it is easy to suppress the viscosity of the film 4 formed by the photosensitive resin composition, and it is possible to improve the insulation reliability and plating resistance of the cured product of the photosensitive resin composition. If the weight average molecular weight of the carboxyl-containing resin (A) is 100,000 or less, the developability of the photosensitive resin composition using an alkaline aqueous solution tends to become good. The weight average molecular weight of the carboxyl-containing resin (A) is more preferably 900 to 60,000, further preferably 1,200 to 10,000, and particularly preferably 1,400 to 5,000. The weight average molecular weight of the carboxyl-containing resin (A) can be calculated, for example, from the measurement results of gel permeation chromatography under the following conditions.
[0069] GPC equipment: SHODEX SYSTEM 11 manufactured by Showa Denko Co., Ltd.
[0070] Column: SHODEX KF-800P, KF-005, KF-003, KF-0014 connected in series,
[0071] Mobile phase: THF,
[0072] Flow rate: 1ml / min,
[0073] Column temperature: 45°C,
[0074] Detector: RI,
[0075] Conversion: Polystyrene.
[0076] The carboxyl group-containing resin (A) preferably contains a component having an acid value of 65 mgKOH / g to 150 mgKOH / g. In this case, the developability of the photosensitive resin composition using an alkaline aqueous solution is particularly improved, and by developing the exposed film 4 using an alkaline aqueous solution, it is particularly easy to produce the through hole 6 having the small diameter portion 63. The acid value is more preferably 70 mgKOH / g to 145 mgKOH / g, further preferably 75 mgKOH / g to 140 mgKOH / g, and particularly preferably 85 mgKOH / g to 135 mgKOH / g.
[0077] The unsaturated compound (B) can impart photocurability to the photosensitive resin composition. The unsaturated compound (B) may contain at least one compound selected from, for example, monofunctional (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, and polyfunctional (meth)acrylates such as diethylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ε-caprolactone-modified pentaerythritol hexaacrylate, and tricyclodecane dimethanol di(meth)acrylate.
[0078] It is particularly preferred that the unsaturated compound (B) contains a trifunctional compound, i.e., a compound having three unsaturated bonds in one molecule. In this case, the resolution when the film 4 formed by the photosensitive resin composition is exposed and developed is improved, and the developability of the photosensitive resin composition using an alkaline aqueous solution is particularly improved. The trifunctional compound may contain, for example, at least one compound selected from trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, ε-caprolactone-modified tri-(2-acryloyloxyethyl) isocyanurate, and ethoxylated glycerol tri(meth)acrylate.
[0079] The unsaturated compound (B) also preferably contains a phosphorus-containing compound (phosphorus-containing unsaturated compound). In this case, the flame retardancy of the cured product of the photosensitive resin composition is improved. The phosphorus-containing unsaturated compound may contain, for example, 2-methacryloyloxyethyl acid phosphate (as a specific example, product numbers LIGHT ESTER P-1M and LIGHT ESTER P-2M manufactured by Kyoeisha Chemical Co., Ltd.), 2-acryloyloxyethyl acid phosphate (as a specific example, product number LIGHT ACRYLATE P-1A), diphenyl-2-methacryloyloxyethyl phosphate (as a specific example, product number MR-260 manufactured by Daihachi Industry Co., Ltd.), and at least one compound of the HFA series manufactured by Showa Polymer Co., Ltd. (as specific examples, product numbers HFA-6003 and HFA-6007 which are addition reaction products of dipentaerythritol hexaacrylate and HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), and product numbers HFA-3003 and HFA-6127 which are addition reaction products of caprolactone-modified dipentaerythritol hexaacrylate and HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide).
[0080] The unsaturated compound (B) may contain a prepolymer. The prepolymer may contain, for example, at least one compound selected from a prepolymer obtained by polymerizing a monomer having an ethylenically unsaturated bond and then adding an ethylenically unsaturated group, and oligomeric (meth)acrylate prepolymers. The oligomeric (meth)acrylate prepolymers may contain, for example, at least one component selected from epoxy (meth)acrylate, polyester (meth)acrylate, urethane (meth)acrylate, alkyd resin (meth)acrylate, silicone resin (meth)acrylate, and spirane resin (meth)acrylate.
[0081] The photopolymerization initiator (C) preferably contains a photopolymerization initiator (C1), which contains at least one selected from an acylphosphine oxide-based photopolymerization initiator, an α-aminoalkylphenone-based photopolymerization initiator, and an oxime ester-based photopolymerization initiator. At this time, when the photosensitive resin composition is exposed to ultraviolet rays, high light absorbency can be imparted to the photosensitive resin composition. If the photosensitive resin composition has good light absorbency, when the film 4 formed by the photosensitive resin composition is exposed, the light is easily absorbed, and thus it is easy to perform photocuring. Furthermore, by absorbing light in the film 4, the amount of light reaching the deep part is reduced. Therefore, it is particularly difficult to produce the influence of light scattering in the deep part, and it is particularly difficult to perform photocuring of the film 4 in the deep part compared to the surface. Therefore, when the through hole 6 is made by photolithography, it is particularly easy to form the small diameter portion 63.
[0082] The photopolymerization initiator (C1) more preferably contains an acylphosphine oxide-based photopolymerization initiator. In this case, higher light absorption can be imparted to the photosensitive resin composition.
[0083] The acylphosphine oxide-based photopolymerization initiator may contain, for example, a monoacylphosphine oxide-based photopolymerization initiator selected from 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, 2,4,6-trimethylbenzoyl-ethyl-phenyl-phosphinate, and bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)- The acylphosphine oxide photopolymerization initiator preferably contains at least one component of a bisacylphosphine oxide photopolymerization initiator such as bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and (2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide. The acylphosphine oxide photopolymerization initiator preferably contains at least one of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and more preferably contains 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide.
[0084] The α-aminoalkylphenone-based photopolymerization initiator may contain, for example, at least one component selected from 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone.
[0085] The oxime ester photopolymerization initiator may contain at least one component selected from, for example, 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)] and ethylone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime).
[0086] The photopolymerization initiator (C) may contain a photopolymerization initiator (C2) containing components other than the above, in addition to the photopolymerization initiator (C1) containing the above components. The photopolymerization initiator (C2) preferably contains at least one of an α-hydroxyacetophenone-based photopolymerization initiator and a thioxanthone-based photopolymerization initiator. In this case, a particularly high light absorption can be imparted to the photosensitive resin composition. The photopolymerization initiator (C2) more preferably contains an α-hydroxyacetophenone-based photopolymerization initiator.
[0087] The α-hydroxyacetophenone-based photopolymerization initiator preferably contains, for example, 1-hydroxycyclohexyl phenyl ketone.
[0088] The thioxanthone-based photopolymerization initiator preferably contains, for example, 2,4-diethylthioxanthene-9-one.
[0089] It is also preferred that the photopolymerization initiator (C) contains 4,4-bis(diethylamino)benzophenone (C3). That is, it is also preferred that the photosensitive resin composition contains a photopolymerization initiator (C1) and 4,4-bis(diethylamino)benzophenone (C3), or contains a photopolymerization initiator (C1), a photopolymerization initiator (C2), and 4,4-bis(diethylamino)benzophenone (C3). In this case, when the film 4 formed by the photosensitive resin composition is partially exposed and then developed, it is particularly easy to suppress the curing of the unexposed portion. Therefore, it is particularly easy to form a through hole 6 having a small diameter portion 63.
[0090] 4,4-bis(diethylamino)benzophenone (C3) is preferably in the range of 0.5% to 20% by mass relative to the photopolymerization initiator (C1). If 4,4-bis(diethylamino)benzophenone (C3) is 0.5% by mass or more, it is particularly easy to suppress the curing of the unexposed portion. In addition, if 4,4-bis(diethylamino)benzophenone (C3) is 20% by mass or less, 4,4-bis(diethylamino)benzophenone (C3) is not likely to hinder the electrical insulation of the cured product of the photosensitive resin composition. Bis(diethylamino)benzophenone (C3) is particularly preferably in the range of 1% to 18% by mass relative to the photopolymerization initiator (C1). When the photosensitive resin composition contains an organic filler (E), the organic filler (E) sometimes generates light scattering in the photosensitive resin composition during exposure. At this time, there may be a problem that good resolution cannot be obtained using the photosensitive resin composition. Therefore, it may be difficult to form a small diameter portion 63 in the through hole 6. However, when the content of 4,4-bis(diethylamino)benzophenone (C3) is within the above range, the photosensitive resin composition tends to have good resolution, and thus the small-diameter portion 63 is particularly easily formed in the through hole 6 .
[0091] The photosensitive resin composition preferably contains an epoxy resin (D). The epoxy resin (D) can impart thermosetting properties to the photosensitive resin composition. The epoxy resin (D) preferably contains a crystalline epoxy resin. In this case, the developability of the photosensitive resin composition can be improved. In addition, the epoxy resin (D) may further contain an amorphous epoxy resin. Here, a "crystalline epoxy resin" is an epoxy resin having a melting point, and an "amorphous epoxy resin" is an epoxy resin having no melting point.
[0092] The crystalline epoxy resin preferably contains, for example, 1,3,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, a hydroquinone type crystalline epoxy resin (a specific example is the trade name YDC-1312 manufactured by Nippon Steel Chemical & Materials Co., Ltd.), a biphenyl type crystalline epoxy resin (a specific example is the trade name YX-4000 manufactured by Mitsubishi Chemical Corporation), a diphenyl ether type crystalline epoxy resin (as a specific example, product number YSLV-80DE manufactured by Nippon Steel Chemicals & Materials Co., Ltd.), bisphenol type crystalline epoxy resin (as a specific example, trade names YSLV-70XY and YSLV-80XY manufactured by Nippon Steel Chemicals & Materials Co., Ltd.), tetraphenolethane type crystalline epoxy resin (as a specific example, product number GTR-1800 manufactured by Nippon Kayaku Co., Ltd.), one or more components of bisphenolfluorene type crystalline epoxy resin.
[0093] The crystalline epoxy resin preferably has two or more epoxy groups in one molecule. In this case, the cured product of the photosensitive resin composition can be made less likely to crack during repeated temperature changes.
[0094] The crystalline epoxy resin preferably has an epoxy equivalent of 150 g / eq to 300 g / eq. The epoxy equivalent is the gram weight of the crystalline epoxy resin containing 1 gram equivalent of epoxy groups. The crystalline epoxy resin has a melting point. Examples of the melting point of the crystalline epoxy resin include 70° C. to 180° C.
[0095] It is particularly preferred that the epoxy compound (D) contains a crystalline epoxy resin having a melting point of 110°C or less. In this case, the developability of the photosensitive resin composition using an alkaline aqueous solution is particularly improved. The crystalline epoxy resin having a melting point of 110°C or less may contain, for example, at least one component selected from a biphenyl type epoxy resin (as a specific example, product number YX-4000 manufactured by Mitsubishi Chemical Corporation), a diphenyl ether type epoxy resin (as a specific example, product number YSLV-80DE manufactured by Nippon Steel Chemical & Materials Co., Ltd.), a bisphenol type epoxy resin (as a specific example, product numbers YSLV-70XY and YSLV-80XY manufactured by Nippon Steel Chemical & Materials Co., Ltd.), and a bisphenol fluorene type crystalline epoxy resin.
[0096] The amorphous epoxy resin preferably contains, for example, a phenol novolac epoxy resin (a specific example is EPICLON N-775 manufactured by DIC Corporation), a cresol novolac epoxy resin (a specific example is EPICLON N-695 manufactured by DIC Corporation), a bisphenol A novolac epoxy resin (a specific example is EPICLON N-865 manufactured by DIC Corporation), a bisphenol A epoxy resin (a specific example is jER1001 manufactured by Mitsubishi Chemical Corporation), a bisphenol F epoxy resin (a specific example is jER4004P manufactured by Mitsubishi Chemical Corporation), a bisphenol S epoxy resin (a specific example is EPICLON N-865 manufactured by DIC Corporation), a bisphenol A epoxy resin (a specific example is jER1001 manufactured by Mitsubishi Chemical Corporation), a bisphenol F epoxy resin (a specific example is jER4004P manufactured by Mitsubishi Chemical Corporation), a bisphenol S epoxy resin (a specific example is EPICLON N-865 manufactured by DIC Corporation), a bisphenol A epoxy resin (a specific example is jER1001 manufactured by Mitsubishi Chemical Corporation), a bisphenol F epoxy resin (a specific example is jER4004P manufactured by Mitsubishi Chemical Corporation), a bisphenol S epoxy resin (a specific example is EPICLON N-865 manufactured by DIC Corporation), a bisphenol A epoxy resin (a specific example is jER1001 manufactured by Mitsubishi Chemical Corporation), a bisphenol S epoxy resin (a specific example is EXA-1514), bisphenol AD type epoxy resin, biphenyl novolac type epoxy resin (as a specific example, Nippon Kayaku Co., Ltd. product number NC-3000), hydrogenated bisphenol A type epoxy resin (as a specific example, Nippon Steel Chemical & Materials Co., Ltd. product number ST-4000D), naphthalene type epoxy resin (as a specific example, DIC Corporation product number EPICLON HP-4032, EPICLON HP-4700, EPICLON HP-4770), tert-butyl catechol type epoxy resin (as a specific example, DIC Corporation product number EPICLON HP-820), dicyclopentadiene type epoxy resin (as a specific example, DIC Corporation product number EPICLON HP-820), HP-7200), adamantane epoxy resin (specifically, ADAMANTATEX-E-201 manufactured by Idemitsu Kosan Co., Ltd.), special difunctional epoxy resin (specifically, YL7175-500 and YL7175-1000 manufactured by Mitsubishi Chemical Corporation; EPICLON TSR-960, EPICLON TER-601, EPILON TSR-250-80BX, EPICLON 1650-75MPX, EPICLON EXA-4850, EPICLON EXA-4816, EPICLON EXA-4822 and EPICLON EXA-9726; product number YSLV-120TE manufactured by Nippon Steel Chemicals & Materials Co., Ltd.), a rubber core-shell polymer modified bisphenol A type epoxy resin (as a specific example, the product number MX-156 manufactured by Kaneka Co., Ltd.), a rubber core-shell polymer modified bisphenol F type epoxy resin (as a specific example, the product number MX-136 manufactured by Kaneka Co., Ltd.), and at least one component of a bisphenol F type epoxy resin containing rubber particles (as a specific example, the product number Kaneace MX-130 manufactured by Kaneka Co., Ltd.).
[0097] When the photosensitive resin composition contains the epoxy resin (D), the photosensitive resin composition preferably contains both a crystalline epoxy resin and an amorphous epoxy resin. In this case, the plating resistance and the insulation properties of the cured product prepared from the photosensitive resin composition can be further improved.
[0098] The epoxy resin (D) may contain a phosphorus-containing epoxy resin. At this time, the flame retardancy of the cured product of the photosensitive resin composition is improved. The phosphorus-containing epoxy resin may be contained in a crystalline epoxy resin, or may be contained in an amorphous epoxy resin. Phosphorus-containing epoxy resins are, for example, phosphoric acid-modified bisphenol F-type epoxy resins (specific examples are EPICLON EXA-9726 and EPICLON EXA-9710 manufactured by DIC Corporation), EPOTOHTOFX-305 manufactured by Nippon Steel Chemical & Materials Co., Ltd., etc.
[0099] The photosensitive resin composition preferably does not contain fillers. In this case, the through hole 6 having the small diameter portion 63 is particularly easily formed by suppressing the scattering of light in the deep part of the film 4. When the photosensitive resin composition contains fillers, the material, particle size and compounding amount of the fillers are preferably appropriately set in a manner that light scattering is not easily generated in the film 4.
[0100] The photosensitive resin composition may contain an organic filler (E). It should be noted that the organic filler (E) does not contain melamine. At this time, it is preferred to appropriately set the material, particle size and compounding amount of the organic filler (E) as described above. The organic filler (E) imparts thixotropy to the photosensitive resin composition, thereby improving the storage stability of the photosensitive resin composition. In addition, the adhesion of the cured product to the plating layer is improved. The organic filler (E) preferably has a reactive group. The organic filler (E) has a high compatibility in the photosensitive resin composition by having a reactive group, and further improves the storage stability of the photosensitive resin composition by imparting a stronger thixotropy to the photosensitive resin composition. In addition, the adhesion of the cured product to the plating layer is further improved. The reactive group possessed by the organic filler (E) more preferably includes at least one group selected from, for example, a carboxyl group, an amino group, an epoxy group, a vinyl group and a hydroxyl group, and further preferably includes at least one of a carboxyl group and an amino group. At this time, the storage stability of the photosensitive resin composition is further improved. In addition, the adhesion of the cured product to the plating layer is further improved. The reactive group possessed by the organic filler (E) particularly preferably includes a carboxyl group. In this case, the developability of the photosensitive resin composition is improved. At the same time, the carboxyl group of the organic filler (E) can react with the epoxy resin (D) in the photosensitive resin composition during thermal curing. Thus, the cured product after thermal curing can contain the organic filler (E) uniformly dispersed therein. Furthermore, the unreacted carboxyl group of the organic filler (E) can also be modified at the stage of roughening the surface of the cured product. That is, the organic filler (E) located near the surface of the cured product in the organic filler (E) contained in the cured product is easily modified at the stage of roughening the surface of the cured product. The organic filler (E) modified in this way is easily removed from the cured product when a rough surface is given to the cured product. Thus, a rough surface can be given to the surface of the cured product to improve the adhesion between the cured product and the plating layer. In addition, the organic filler (E) contains a carboxyl group, which can reduce the unevenness of the coating film caused by the fluidity of the photosensitive resin composition. Thus, it is easy to make the film thickness of the layer formed by the photosensitive resin composition uniform. Furthermore, it is easy to form the through hole 6 having the small diameter portion 63 in the interlayer insulating layer 7 made of the photosensitive resin composition.
[0101] When the organic filler (E) contains a carboxyl group, the carboxyl group can be formed as a side chain in the product by, for example, polymerizing or cross-linking carboxylic acid monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid. The carboxylic acid monomer has a carboxyl group and a polymerizable unsaturated double bond. The organic filler (E) can improve the stability (especially storage stability) of the photosensitive resin composition by improving the thixotropy of the photosensitive resin composition. Furthermore, if the organic filler (E) contains a carboxyl group, the developability of the cured product can be improved, and the compatibility of the crystalline epoxy resin can be improved to prevent crystallization in the photosensitive resin composition. The carboxyl content of the organic filler (E) is not particularly limited, and the acid value of the organic filler (E) is preferably 1 mgKOH / g to 60 mgKOH / g based on the acid value of acid-base titration. If the acid value is less than 1 mgKOH / g, the stability of the photosensitive resin composition and the developability of the cured product may be reduced. If the acid value is greater than 60 mgKOH / g, the moisture resistance reliability of the cured product may be reduced. The acid value of the organic filler (E) is more preferably 3 mgKOH / g to 40 mgKOH / g.
[0102] The average primary particle size of the organic filler (E) is preferably 1 μm or less. When the average primary particle size of the organic filler (E) is 1 μm or less, the developability of the photosensitive resin composition becomes good. In addition, the roughness of the rough surface formed on the cured product can be made finer, and as the surface area of the cured product increases, the anchoring effect becomes larger, and the adhesion between the rough surface and the plating layer can be improved.
[0103] The lower limit of the average primary particle size of the organic filler (E) is not particularly limited, but is preferably 0.001 μm or more, for example. The average primary particle size is measured using a laser diffraction particle size distribution measuring apparatus as D 50 The average primary particle size of the organic filler (E1) is more preferably 0.4 μm or less, and further preferably 0.1 μm or less. In this case, the scattering of light in the photosensitive resin composition during exposure can be suppressed, thereby further improving the resolution of the photosensitive resin composition, and making it easy to form a through hole 6 having a small diameter portion 63 in the interlayer insulating layer 7. In addition, the roughness of the rough surface formed on the cured product can be made particularly fine.
[0104] The organic filler (E) is preferably dispersed in the photosensitive resin composition with a maximum particle size of less than 1.0 μm, and more preferably dispersed with a maximum particle size of less than 0.5 μm. The maximum particle size is measured by laser diffraction particle size distribution measuring apparatus, D 50Or the maximum particle size is measured by observing the cured product using a transmission electron microscope (TEM). The organic filler (E) sometimes aggregates in the photosensitive resin composition (for example, secondary particles can be formed). In this case, the maximum particle size refers to the size of the particles after aggregation. If the maximum particle size of the organic filler (E) in a dispersed state is within the above range, scattering during exposure is suppressed in the photosensitive resin composition, thereby further improving the resolution of the photosensitive resin composition and making it easier to form a through hole 6 having a small diameter portion 63 in the interlayer insulating layer 7. In addition, the roughness of the rough surface formed on the cured product can be made finer. It should be noted that when aggregation of particles occurs, the maximum particle size is usually larger than the average primary particle size.
[0105] The organic filler (E) preferably contains a rubber component. In addition, the organic filler (E) preferably contains only a rubber component. The rubber component can impart flexibility to the cured product of the photosensitive resin composition. The rubber component can be composed of a resin. The rubber component preferably contains at least one polymer selected from cross-linked acrylic rubber, cross-linked NBR, cross-linked MBS and cross-linked SBR. At this time, the rubber component can impart excellent flexibility to the cured product of the photosensitive resin composition. Furthermore, a more appropriate rough surface can be imparted to the surface of the cured product. Here, the rubber component contains a cross-linked structure formed when the monomers constituting the polymer are copolymerized. NBR is generally a copolymer of butadiene and acrylonitrile, and is classified as nitrile rubber. MBS is generally a copolymer composed of three components, methyl methacrylate, butadiene, and styrene, and is classified as butadiene-based rubber. SBR is generally a copolymer of styrene and butadiene, and is classified as styrene rubber. Specific examples of organic fillers (E) include product number XER-91-MEK manufactured by JSR Corporation, product number XER-32-MEK manufactured by JSR Corporation, and product number XSK-500 manufactured by JSR Corporation. XER-91-MEK is a cross-linked rubber (NBR) having a carboxyl group with an average primary particle size of 0.07 μm, provided as a methyl ethyl ketone dispersion containing 15% by weight of the cross-linked rubber, and having an acid value of 10.0 mgKOH / g. XER-32-MEK is a dispersion obtained by dispersing a polymer (linear particles) of carboxyl-modified hydrogenated nitrile rubber in methyl ethyl ketone in a content of 17% by weight relative to the total amount of the dispersion. In addition, XSK-500 is a cross-linked rubber (SBR) having a carboxyl group and a hydroxyl group with an average primary particle size of 0.07 μm, provided as a methyl ethyl ketone dispersion containing 15% by weight of the cross-linked rubber. In this way, the organic filler (E) can be mixed in the photosensitive resin composition in the form of a dispersion. That is, the rubber component can be mixed in the photosensitive resin composition in the form of a dispersion. In addition, as a specific example of the organic filler (E), in addition to the above, product number XER-92 manufactured by JSR Corporation can be cited.
[0106] The photosensitive resin composition may contain a silane coupling agent. In this case, the dispersibility of the organic filler (E) can be improved and the resolution of the photosensitive resin composition can be further improved.
[0107] The silane coupling agent is, for example, a compound containing a silicon atom and 2 to 4 hydrolyzable groups selected from -OCH3, -OC2H5 and -OCOCH3. In addition to the hydrolyzable groups, the silane coupling agent may also contain reactive groups such as amino, epoxy, vinyl (allyl), methacryloyl, mercapto, isocyanate, thioether, or methyl groups.
[0108] Examples of the silane coupling agent include amino compounds such as 3-(2-aminoethylamino)propyldimethoxymethylsilane, 3-(2-aminoethylamino)propyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, 3-aminopropyldiethoxymethylsilane, 3-aminopropyltriethoxysilane, and 3-aminopropyltrimethoxysilane; epoxies such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyl(dimethoxy)methylsilane, and diethoxy(3-glycidoxypropyl)methylsilane; and 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxypropylmethylsilane. (Meth)acrylates such as trimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyl compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, p-phenylenetrimethoxysilane, diethoxymethylvinylsilane, and vinyltri(2-methoxyethoxy)silane, allyl compounds such as allyltriethoxysilane and allyltrimethoxysilane, styrene compounds such as p-phenylenetrimethoxysilane, isocyanates such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane, ureas such as 3-ureapropyltrimethoxysilane and 3-ureapropyltriethoxysilane, mercapto compounds such as (3-mercaptopropyl)triethoxysilane and (3-mercaptopropyl)trimethoxysilane, sulfide ethers such as bis(triethoxysilylpropyl)tetrasulfide, tetraethyl orthosilicate, methyltrimethoxysilane, and the like.
[0109] The photosensitive resin composition may contain melamine. In this case, the degree to which the cured product of the photosensitive resin composition is corroded by an oxidant such as potassium permanganate can be significantly reduced. That is, by containing melamine in the photosensitive resin composition, when the surface of the cured product of the photosensitive resin composition is roughened in the pre-plating process, the thickness of the layer containing the cured product can be made less likely to become thinner. By giving the cured product a rough surface in this way, the adhesion between the cured product of the photosensitive resin composition and the plating layer composed of copper, gold, etc. can be improved. Melamine is 2,4,6-triamino-1,3,5-triazine, which can generally be obtained from commercially available compounds. Melamine is preferably dispersed in the photosensitive resin composition with an average particle size of less than 20 μm, preferably less than 15 μm. By uniformly dispersing melamine in the photosensitive resin composition, melamine is further easily coordinated and bonded with metal elements. Thus, the adhesion of the photosensitive resin composition can be further improved. The lower limit of the average particle size of melamine is not particularly limited, and may be 0.01 μm or more. It should be noted that the average particle size of melamine is obtained by using a laser diffraction particle size distribution measuring device in a state where melamine is dispersed in an uncured photosensitive resin composition, with a particle size distribution of D 50 Measured in the form of.
[0110] The photosensitive resin composition may contain an inorganic filler. In this case, the curing shrinkage of the film formed by the photosensitive resin composition is reduced. In addition, the dielectric loss tangent can be reduced. The inorganic filler may contain, for example, one or more materials selected from barium sulfate, silicon dioxide, carbon nanotubes, talc, bentonite, aluminum hydroxide, magnesium hydroxide and titanium oxide.
[0111] The photosensitive resin composition of the present embodiment may contain an organic solvent. The organic solvent is used for the purpose of liquefying or varnishing the photosensitive resin composition, adjusting viscosity, adjusting coating properties, adjusting film-forming properties, and the like.
[0112] The organic solvent may contain, for example, linear, branched, dihydric or polyhydric alcohols selected from ethanol, propanol, isopropanol, hexanol, ethylene glycol, etc.; ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene and xylene; petroleum-based aromatic mixed solvents such as Swasol series (manufactured by Maruzen Petrochemical Co., Ltd.) and Solvesso series (manufactured by Exxon Chemical Co., Ltd.); cellosolves such as cellosolve and butyl cellosolve; carbitols such as carbitol and butyl carbitol; propylene glycol alkyl ethers such as propylene glycol methyl ether; polypropylene glycol alkyl ethers such as dipropylene glycol methyl ether; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, carbitol acetate; and one or more compounds selected from dialkyl glycol ethers.
[0113] The carboxyl group-containing resin (A) is preferably in the range of 5% to 85% by mass relative to the solid content of the photosensitive resin composition, more preferably in the range of 10% to 75% by mass, and even more preferably in the range of 30% to 60% by mass. It should be noted that the solid content refers to the total amount of all components excluding volatile components such as solvents in the photosensitive resin composition.
[0114] It is preferred if the unsaturated compound (B) having at least one ethylenically unsaturated bond in one molecule is within the range of 5% to 45% by mass relative to the carboxyl-containing resin (A). By having the unsaturated compound (B) within this range, it is particularly easy to make the through hole 6 having the small diameter portion 63. It is more preferred if the unsaturated compound (B) is within the range of 10% to 42% by mass relative to the carboxyl-containing resin (A), and it is further preferred if it is within the range of 21% to 40% by mass.
[0115] It is preferred if the photopolymerization initiator (C) is in the range of 1% to 30% by mass relative to the carboxyl-containing resin (A). If the proportion of the photopolymerization initiator (C) relative to the carboxyl-containing resin (A) is 1% by mass or more, the photosensitive resin composition tends to have good light absorption. Since the photosensitive resin composition has good light absorption, it is easy to increase the degree of curing of the surface of the interlayer insulating layer 7, and the water absorption of the interlayer insulating layer 7 can be reduced. In addition, it is easier to form a through hole 6 having a small diameter portion 63 in the interlayer insulating layer 7. If the photopolymerization initiator (C) is 30% by mass or less relative to the carboxyl-containing resin (A), the cured film of the photosensitive resin composition tends to have good electrical insulation.
[0116] The photopolymerization initiator (C) is more preferably in the range of 1.5 to 25% by mass, further preferably in the range of 2 to 20% by mass, and particularly preferably in the range of 3 to 10% by mass, relative to the carboxyl group-containing resin (A).
[0117] When the photosensitive resin composition contains an epoxy resin (D), the total equivalent of the epoxy group contained in the epoxy resin (D) is preferably 0.1 to 5 relative to 1 equivalent of the carboxyl group of the carboxyl group-containing resin (A). When the equivalent of the epoxy group of the epoxy resin (D) is 0.1 or more relative to 1 equivalent of the carboxyl group of the carboxyl group-containing resin (A), thermosetting properties can be imparted to the photosensitive resin composition. When the equivalent of the epoxy group of the epoxy resin (D) is 5 or less relative to 1 equivalent of the carboxyl group of the carboxyl group-containing resin (A), the photosensitive resin composition has good developability. The equivalent of the epoxy group of the epoxy resin (D) is more preferably 0.3 to 4, further preferably 0.5 to 3, and particularly preferably 0.7 to 2 relative to 1 equivalent of the carboxyl group of the carboxyl group-containing resin (A).
[0118] The content of the organic filler (E) is preferably 1% to 100% by mass relative to the carboxyl-containing resin (A). By having an organic filler (E) content of 1% by mass or more, the surface of the cured product of the photosensitive resin composition can be appropriately roughened, thereby improving the adhesion between the rough surface of the cured product and the plating layer. By having an organic filler (E) content of 100% by mass or less, the photosensitive resin composition is easily developed. The content of the organic filler (E) is more preferably 1.5% to 50% by mass, more preferably 2% to 30% by mass, and particularly preferably 3% to 20% by mass relative to the carboxyl-containing resin (A). At this time, it is particularly easy to make a through hole 6 having a small diameter portion 63.
[0119] When the photosensitive resin composition contains a silane coupling agent, the content of the silane coupling agent is preferably 0.01% to 7% by mass relative to the organic filler (E). When the proportion of the silane coupling agent is within this range, the agglomeration of the organic filler (E) in the photosensitive resin composition can be prevented, and the dispersibility is improved. The proportion of the silane coupling agent is more preferably 0.05% to 5% by mass relative to the organic filler (E). When the proportion of the silane coupling agent is within this range, the agglomeration of the organic filler (E1) in the photosensitive resin composition can be more efficiently prevented, and the dispersibility is more effectively improved.
[0120] When the photosensitive resin composition contains melamine, the content of melamine is preferably 0.1% to 10% by mass relative to the carboxyl group-containing resin (A). In this case, the composition exhibits good developability in an alkaline aqueous solution, and it is easier to form the through hole 6 having the small diameter portion 63 in the interlayer insulating layer 7. The content of melamine is more preferably 0.3% to 9% by mass, further preferably 0.5% to 8% by mass, and particularly preferably 1% to 6% by mass relative to the carboxyl group-containing resin (A).
[0121] The ratio of the inorganic filler in the photosensitive resin composition can be appropriately set, and the content of the inorganic filler is preferably 0% to 200% by mass relative to the carboxyl-containing resin (A). In this case, good resolution can be obtained, and it is easier to form the through hole 6 having the small diameter portion 63 in the interlayer insulating layer 7. The content of the inorganic filler is more preferably 0% to 150% by mass, more preferably 0% to 100% by mass, more preferably 0% to 50% by mass, and particularly preferably 0% to 20% by mass relative to the carboxyl-containing resin (A).
[0122] When the photosensitive resin composition contains an organic solvent, the amount of the organic solvent is preferably adjusted in such a way that the organic solvent volatilizes rapidly when the coating film formed by the photosensitive resin composition is dried, that is, the organic solvent does not remain in the dried film. In particular, the proportion of the organic solvent is preferably 0% to 99.5% by mass relative to the entire photosensitive resin composition, and is further preferably 15% to 60% by mass. It should be noted that the preferred proportion of the organic solvent varies depending on the coating method, etc., and it is preferred to appropriately adjust the proportion according to the coating method.
[0123] The photosensitive composition may further contain components other than the above components unless the effects of the present embodiment are impaired.
[0124] The photosensitive resin composition may contain blocked isocyanates selected from toluene diisocyanate series, morpholine diisocyanate series, isophorone diisocyanate series and hexamethylene diisocyanate series blocked with caprolactam, oxime, malonate, etc.; butylated urea resin; various thermosetting resins other than the above; ultraviolet curable epoxy (meth) acrylate; a resin obtained by adding (meth) acrylic acid to epoxy resins of bisphenol A type, phenol novolac type, cresol novolac type, alicyclic type, etc.; and at least one resin selected from polymer compounds such as diallyl phthalate resin, phenoxy resin, urethane resin, melamine resin, fluororesin, etc.
[0125] The photosensitive resin composition may contain a curing agent for curing the epoxy compound (D). The curing agent may contain, for example, imidazole derivatives selected from imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, etc.; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, 4-methyl-N,N-dimethylbenzylamine, etc.; hydrazine compounds such as adipic acid hydrazide and sebacic acid hydrazide; phosphorus compounds such as triphenylphosphine; acid anhydrides; phenols; thiols; Lewis acid amine complexes; and At least one component in the salt. Commercially available products of these components include, for example, 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ (all trade names of imidazole compounds) manufactured by Shikoku Chemicals Co., Ltd., U-CAT3503N, UCAT3502T (all trade names of blocked isocyanate compounds of dimethylamine) manufactured by San-Apro Co., Ltd., DBU, DBN, U-CATSA102, U-CAT5002 (all bicyclic amidine compounds and salts thereof).
[0126] The photosensitive resin composition may contain an adhesion-imparting agent. Examples of the adhesion-imparting agent include guanamine derivatives such as acetoguanamine (2,4-diamino-6-methyl-1,3,5-triazine) and benzoguanamine (2,4-diamino-6-phenyl-1,3,5-triazine), s-triazine derivatives such as 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2-vinyl-4,6-diamino-s-triazine, 2-vinyl-4,6-diamino-s-triazine·isocyanuric acid adduct, 2,4-diamino-6-methacryloyloxyethyl-s-triazine·isocyanuric acid adduct, silane coupling agents, melamine derivatives, and the like.
[0127] The photosensitive resin composition may contain a rheology control agent. The rheology control agent can easily optimize the viscosity of the photosensitive resin composition. Examples of the rheology control agent include urea-modified neutral polar polyamides (BYK-430 and BYK-431 manufactured by BYK Chemie Japan Co., Ltd.), polyhydroxycarboxylic acid amides (BYK-405 manufactured by BYK Chemie Japan Co., Ltd.), modified ureas (BYK-410, BYK-411, and BYK-420 manufactured by BYK Chemie Japan Co., Ltd.), polymer urea derivatives (BYK Chemie Japan Co., Ltd., BYK-415), urea-modified urethanes (BYK Chemie Japan Co., Ltd., BYK-425), polyurethanes (BYK Chemie Japan Co., Ltd., BYK-428), castor oil wax, polyethylene wax, polyamide wax, bentonite, kaolin, and clay.
[0128] The photosensitive resin composition may contain at least one component selected from a curing accelerator, a colorant, a copolymer of silicone, acrylate, etc., a leveling agent, a thixotropic agent, a polymerization inhibitor, an antihalation agent, a flame retardant, a defoaming agent, an antioxidant, a surfactant, and a polymer dispersant.
[0129] When preparing the photosensitive resin composition of the present embodiment, it can be prepared by an appropriate method. For example, the photosensitive resin composition can be prepared by mixing and stirring the raw materials of the photosensitive resin composition. In addition, the photosensitive resin composition can be prepared by mixing using an appropriate mixing method such as a three-roll mill, a ball mill, a sand mill, etc. When the raw material contains liquid components, low-viscosity components, etc., the raw material can first be mixed with the parts other than the liquid components, low-viscosity components, etc. to prepare the mixture, and then the liquid components, low-viscosity components, etc. are added to the obtained mixture for mixing, thereby preparing the photosensitive resin composition. When the photosensitive resin composition contains a solvent (E), a part or all of the solvent in the raw material can be mixed first, and then mixed with the remaining raw materials.
[0130] The photosensitive resin composition preferably has the following properties: even if the film 4 has a thickness of 25 μm, it can be developed with a sodium carbonate aqueous solution. In this case, a sufficiently thick electrically insulating layer can be produced from the photosensitive resin composition by photolithography, so the photosensitive resin composition can be widely used to produce the interlayer insulating layer 7 in the printed wiring board 11. Of course, an electrically insulating layer thinner than 25 μm in thickness can also be produced from the photosensitive resin composition.
[0131] Whether the film 4 with a thickness of 25 μm can be developed using a sodium carbonate aqueous solution can be confirmed by the following method. A wet coating film is prepared by coating a photosensitive resin composition on an appropriate substrate 1, and the wet coating film is heated at 80°C for 40 minutes to form a film 4 with a thickness of 25 μm. A negative mask having an exposure portion that transmits ultraviolet rays and a non-exposure portion that blocks ultraviolet rays is directly placed against the film 4, and the film is exposed to the light at a rate of 500 mJ / cm 2 The film 4 is exposed to ultraviolet light under the conditions of. After exposure, the film 4 is sprayed with a 1% Na2CO3 aqueous solution at 30°C at a spray pressure of 0.2 MPa for 90 seconds, and then pure water is sprayed at a spray pressure of 0.2 MPa for 90 seconds. The film 4 is observed after the treatment. As a result, when the portion of the film 4 corresponding to the non-exposed portion is removed and no residue is confirmed, it can be determined that the film 4 with a thickness of 25 μm can be developed using a sodium carbonate aqueous solution. It should be noted that for films 4 of other thicknesses (for example, 30 μm), it can also be confirmed whether they can be developed using a sodium carbonate aqueous solution.
[0132] (2.2) Manufacturing of Printed Wiring Board 11
[0133] Reference Figure 1A to Figure 1E A method for manufacturing printed wiring board 11 according to the present embodiment will be described.
[0134] When manufacturing the printed wiring board 11, for example, a photosensitive resin composition and a substrate are prepared. The substrate has an insulating layer 2 and a second conductor layer 3 superimposed on the insulating layer 2. A film 4 made of a photosensitive resin composition is superimposed on the substrate so as to cover the second conductor layer 3, and a negative pattern region of the film 4 including a pattern of a through hole 6 is exposed, and then a development treatment is performed using an alkaline aqueous solution. In this way, an interlayer insulating layer 7 and a through hole 6 penetrating the interlayer insulating layer 7 are produced.
[0135] Specifically, for example, first, Figure 1A As shown, a base material 1 is prepared. The base material 1 includes an insulating layer 2 and a second conductor layer 3. The second conductor layer 3 is a conductor wiring.
[0136] The photosensitive resin composition is applied on the substrate and further dried as required. Figure 1B As shown in the figure, the film 4 covering the second conductor layer 3 is thus prepared. The coating method of the photosensitive resin composition is selected from a known method, such as dipping, spraying, spin coating, roll coating, curtain coating and screen printing. When the photosensitive resin composition is dried, the photosensitive resin composition is heated at a temperature of, for example, 60° C. to 130° C.
[0137] The film 4 can be formed by overlapping a dry film made of a photosensitive resin composition on a substrate. The dry film is formed on a support by, for example, applying the photosensitive resin composition on a suitable support such as polyester and then drying it. Thus, a dry film with a support having a dry film and a support for supporting the dry film can be obtained. After the dry film of the dry film with a support is overlapped on the substrate 1 so as to cover the second conductor layer 3, pressure is applied to the dry film and the substrate 1. Thus, the film 4 composed of the dry film is overlapped on the substrate 1.
[0138] Next, the film 4 is exposed. For example, the negative pattern region of the film 4 including the pattern of the through hole 6 is exposed. At this time, for example, the film 4 is irradiated with ultraviolet rays through a negative mask. The negative mask has an exposure portion that transmits ultraviolet rays and a non-exposure portion that blocks ultraviolet rays, and the pattern of the non-exposure portion includes the pattern of the through hole 6. The negative mask is, for example, an optical tool such as a mask film or a dry plate. The light source of ultraviolet rays is, for example, selected from a chemical lamp, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, and a metal halide lamp.
[0139] When the film 4 is made of a dry film, the film 4 is exposed, for example, after the support is peeled off from the film 4 in advance, the film 4 is exposed. It should be noted that the film 4 may be exposed by irradiating ultraviolet rays through the support while the support is overlapped with the film 4, and then the support is peeled off from the film 4 after exposure.
[0140] As an exposure method, a method other than the method using a negative mask may be used. For example, the film 4 may be exposed by a direct drawing method in which ultraviolet rays emitted from a light source are irradiated only on the portion to be exposed on the film 4. The light source used in the direct drawing method is selected from, for example, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, g-rays (436 nm), h-rays (405 nm), i-rays (365 nm), and a combination of two or more of g-rays, h-rays, and i-rays.
[0141] The ultraviolet rays irradiated to the film 4 preferably have a spectral intensity at at least one wavelength in the wavelength region of 365nm±65nm. In addition, the ultraviolet rays irradiated to the film 4 preferably do not have a spectral intensity at a wavelength of 435nm or more. By having the ultraviolet rays irradiated to the film 4 have a spectral intensity at at least one wavelength in the wavelength region of 365nm±65nm, the film 4 is easily cured. In addition, if the ultraviolet rays include light with a wavelength of 435nm or more, the diameter of the second end 62 of the through hole 6 formed in the interlayer insulating layer 7 is likely to become smaller after development. It is speculated that the reason is that the long-wavelength light of 435nm or more is not easily absorbed by the photosensitive resin composition and easily reaches the deep part of the film 4, and light scattering is likely to occur in the deep part of the film 4. The ultraviolet light irradiating the film 4 further preferably has spectral intensity at at least one wavelength in the wavelength region of 365nm±45nm and has no spectral intensity above 415nm, further preferably has spectral intensity at at least one wavelength in the wavelength region of 365nm±30nm and has no spectral intensity above 400nm, and particularly preferably has spectral intensity at at least one wavelength in the wavelength region of 365nm±15nm and has no spectral intensity above 385nm.
[0142] Next, the film 4 is developed with an alkaline aqueous solution to form an interlayer insulating layer 7 having a through hole 6. At this time, as described above, the through hole 6 having a small diameter portion 63 is easily formed. By performing the development treatment on the film 4, the film 4 is removed. Figure 1C The non-cured portion 5 of the film 4 shown, whereby Figure 1DA through hole 6 is provided as shown. In the development process, an appropriate developer corresponding to the composition of the photosensitive resin composition can be used. The developer is, for example, an alkaline aqueous solution containing at least one of an alkali metal salt and an alkali metal hydroxide, or an organic amine. More specifically, the alkaline aqueous solution contains, for example, at least one component selected from the group consisting of sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, sodium hydroxide, potassium hydroxide, ammonium hydroxide, tetramethylammonium hydroxide and lithium hydroxide. The solvent in the alkaline aqueous solution may be water alone, or a mixture of water and a hydrophilic organic solvent such as a lower alcohol. The organic amine contains, for example, at least one component selected from the group consisting of monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine and triisopropanolamine.
[0143] The alkaline aqueous solution preferably contains at least one of an alkali metal salt and an alkali metal hydroxide, and particularly preferably contains sodium carbonate. In this case, it is possible to improve the working environment and reduce the burden of waste treatment.
[0144] Since the photosensitive resin composition of the present embodiment has good developability, after development, uncured photosensitive resin composition residues are unlikely to remain at the bottom of the through hole 6. Therefore, the through hole 6 having the small diameter portion 63 can be easily formed.
[0145] Next, the developed film 4 can be thermally cured by heating. The heating conditions are, for example, a heating temperature in the range of 120° C. to 200° C. and a heating time in the range of 20 minutes to 180 minutes. If the film 4 is thermally cured in this way, the interlayer insulating layer 7 is improved in strength, hardness, chemical resistance, and other properties.
[0146] If necessary, ultraviolet rays may be further irradiated to the film 4 before or after heating, or both of them. In this case, the film 4 can be further photocured.
[0147] Through the above operation, an interlayer insulating layer 7 composed of a cured product of a photosensitive resin composition is provided on the substrate 1. Next, a first conductor layer 8 as a conductor wiring can be formed on the interlayer insulating layer 7 by a known method such as an additive method, and a via conductor 9 can be formed in the through hole 6. Figure 1E As shown in FIG. 1 , a printed wiring board 11 including a first conductor layer 8, a second conductor layer 3, an interlayer insulating layer 7, a through hole 6, and a via conductor 9 is obtained. Figure 1E In the embodiment, via conductor 9 is filled entirely in through hole 6 , but via conductor 9 may be a film covering the inner surface of through hole 6 .
[0148] Furthermore, the entire inner surface of through hole 6 and a portion of the outer surface of interlayer insulating layer 7 may be roughened before forming via conductor 9. In this case, the adhesion between substrate 1 and via conductor 9 can be improved.
[0149] The roughening of a part of the outer surface of the interlayer insulating layer 7 and the entire inner surface of the through hole 6 can be performed in the same steps as the general desmearing process using an oxidant. For example, the outer surface of the interlayer insulating layer 7 is roughened by bringing the oxidant into contact with the outer surface of the interlayer insulating layer 7. However, this is not limited to this, and an appropriate roughening method such as plasma treatment, UV treatment, ozone treatment, etc. can also be used.
[0150] The oxidant may be an oxidant that can be obtained as a desmear solution. Such an oxidant may contain, for example, at least one permanganate selected from sodium permanganate and potassium permanganate.
[0151] When providing via conductor 9, an initial conductor may be formed by electroless metal plating a portion of the roughened outer surface and the inner surface of through hole 6. Thereafter, via conductor 9 is formed by depositing metal in the plating solution on the initial conductor by electrolytic metal plating.
[0152] Example
[0153] The present disclosure is specifically described below through examples, but the present disclosure is not limited to the following examples, and various changes can be made according to the design as long as the purpose of the present disclosure can be achieved.
[0154] 1. Synthesis of carboxyl-containing resin
[0155] [Synthesis Examples 1 to 6: Resins containing a bisphenol fluorene skeleton]
[0156] The components shown in the "First Reaction" column in Table 1 were added to a four-necked flask equipped with a reflux cooler, a thermometer, an air blowing tube, and a stirrer, and stirred under air bubbling to prepare a mixture. The mixture was heated in the flask at the reaction temperature and reaction time shown in the "Reaction Conditions" column while stirring under air bubbling. Thus, a solution of an intermediate was prepared.
[0157] Next, the components shown in the "second reaction" column of Table 1 were added to the solution of the intermediate in the flask, and heated according to the reaction temperature and reaction time shown in the "reaction conditions (1)" column while stirring under air bubbling. Next, heated according to the reaction temperature and reaction time shown in the "reaction conditions (2)" column while stirring under air bubbling. Thus, a 65% by mass solution of carboxyl-containing resin was obtained. The weight average molecular weight and acid value of the carboxyl-containing resin are shown in Table 1.
[0158] In addition, the details of the components shown in the column (a1) in Table 1 are as follows.
[0159] Epoxy compound 1: a bisphenol fluorene-type epoxy compound represented by formula (2) and having an epoxy equivalent of 250 g / eq, wherein all of R1 to R8 in formula (2) are hydrogen.
[0160] Epoxy compound 2: a bisphenol fluorene-type epoxy compound represented by formula (2) with an epoxy equivalent of 279 g / eq, wherein R1 and R5 in formula (2) are both methyl groups, and R2 to R4 and R6 to R8 are all hydrogen.
[0161] [Synthesis Example 7: Resin containing a biphenyl novolac skeleton]
[0162] In a four-necked flask equipped with a reflux cooler, a thermometer, an air blowing tube and a stirrer, 288 parts by mass of a biphenyl novolac epoxy resin (manufactured by Nippon Kayaku Co., Ltd., product number NC-3000-H, epoxy equivalent 288 g / eq), 155 parts by mass of diethylene glycol monoethyl ether acetate, 0.2 parts by mass of methylhydroquinone, 72 parts by mass of acrylic acid and 3 parts by mass of triphenylphosphine were added to prepare a mixture. The mixture was heated at a temperature of 115° C. for 12 hours while stirring under air bubbling in the flask. Thus, a solution of an intermediate was prepared.
[0163] Next, 85 parts by mass of tetrahydrophthalic anhydride and 86.3 parts by mass of diethylene glycol monoethyl ether acetate were added to the solution of the intermediate in the flask, and heated at 90° C. for 4 hours while stirring under air bubbling. Thus, a 65% by mass solution of carboxyl-containing resin B-1 was obtained. The weight average molecular weight of carboxyl-containing resin B-1 was 8026, and the acid value was 69 mgKOH / g.
[0164] 2. Preparation of the composition
[0165] The components shown in Tables 2 to 3 described later were kneaded with a three-roll mill and then stirred and mixed in a flask to obtain a composition. The details of the components shown in Tables 2 to 3 are as follows.
[0166] Unsaturated compound A: trimethylolpropane triacrylate.
[0167] Photopolymerization initiator A: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, manufactured by BASF, product number Irgacure TPO.
[0168] Photopolymerization initiator B: 1-hydroxy-cyclohexyl-phenyl-ketone, manufactured by BASF, product number Irgacure184.
[0169] Photopolymerization initiator C: 4,4'-bis(diethylamino)benzophenone.
[0170] Photopolymerization initiator D: 2,4-diethylthioxanthen-9-one.
[0171] Crystalline epoxy resin A: bisphenol-type crystalline epoxy resin, product number YSLV-80XY manufactured by Nippon Steel Chemicals & Materials Co., Ltd., melting point 75 to 85° C., epoxy equivalent 192 g / eq.
[0172] Amorphous epoxy resin solution A: A solution prepared by dissolving a bisphenol A type epoxy resin containing a long carbon chain (manufactured by DIC Corporation, product number EPICLON EXA-4816, liquid resin, epoxy equivalent 410 g / eq) in diethylene glycol monoethyl ether acetate at a solid content of 90%.
[0173] Organic filler A dispersion: a dispersion prepared by dispersing a crosslinked rubber (NBR) having an average primary particle size of 0.07 μm in methyl ethyl ketone at a content of 15 wt % based on the total amount of the dispersion (manufactured by JSR Corporation, product number XER-91-MEK; acid value 10.0 mgKOH / g).
[0174] Organic filler B: glycidyl-modified acrylonitrile-butadiene rubber having an average primary particle size of 0.3 μm.
[0175] Additive A: 3-glycidoxypropyltrimethoxysilane.
[0176] Additive B: melamine.
[0177] Solvent A: methyl ethyl ketone.
[0178] 3. Evaluation of composition
[0179] (1) Preparation of test pieces
[0180] A test piece was prepared as follows using the composition of each composition example.
[0181] The composition of each composition example was applied onto a polyethylene terephthalate film using an applicator, and then dried by heating at 80° C. for 5 minutes and then at 95° C. for 20 minutes to form a dry film having a thickness of 35 μm on the film.
[0182] A glass epoxy copper clad laminate (FR-4 type) with a thickness of 17.5 μm and copper foil is prepared. The surface portion of the glass epoxy copper clad laminate with a thickness of about 1 μm is treated with an etchant (product number CZ-8101 manufactured by MEC Co., Ltd.) to perform roughening. The dry film is heat-laminated on the entire surface of one side of the glass epoxy copper clad laminate using a vacuum laminator. The conditions for the heat lamination are set to 0.5 MPa, 80°C, and 1 minute. Thus, a coating composed of the dry film is formed on the glass epoxy copper clad laminate. Through a negative mask having a non-exposed portion and a film made of polyethylene terephthalate, at a cumulative light intensity of 250 mJ / cm 2The film was irradiated with ultraviolet rays having a wavelength of 365 nm under the condition of , and the non-exposed portion had a pattern including a circular shape having a diameter of 80 μm. Next, the polyethylene terephthalate film was peeled off from the film.
[0183] Next, an alkaline aqueous solution (1% Na2CO3 aqueous solution) at 30°C was sprayed on the film at a spray pressure of 0.2 MPa for 90 seconds, and then pure water was sprayed at a spray pressure of 0.2 MPa for 90 seconds to develop the film. Next, the film was heated at 180°C for 120 minutes. Thus, an interlayer insulating layer and a through hole penetrating the interlayer insulating layer were formed on the printed wiring board. Thus, a test piece was obtained.
[0184] The test pieces were evaluated as follows. In Composition Example 11, development was not possible and no evaluation was performed. In Composition Example 14, there were portions where film peeling due to insufficient curing was observed during development and no evaluation was performed.
[0185] (2) Determination of the diameter of the first end and the diameter of the second end
[0186] The specimen was cut in two on a plane parallel to the axis of the through hole, and the cross section was photographed using an electron microscope (SEM). Based on the image obtained, the diameter of the first end and the diameter of the second end of the through hole were measured. In addition, the value of (diameter of the first end ÷ diameter of the second end) × 100 (%) was calculated.
[0187] (3) Whether there is a small diameter section
[0188] Based on the image obtained in the above “(2) Measurement of the diameter of the first end and the diameter of the second end”, it was confirmed whether there was a small diameter portion between the first end and the second end of the through hole, and the evaluation was performed as follows.
[0189] A: There is a small-diameter portion between the first end and the second end, and the minimum diameter of the small-diameter portion is 65% or more and less than 100% of the diameter of the second end.
[0190] B: There is a small diameter portion between the first end and the second end, and the minimum diameter of the small diameter portion is less than 65% of the diameter of the second end.
[0191] C: There is no small diameter portion between the first end and the second end.
[0192] (4) Path shape evaluation
[0193] Based on the images obtained in the above-mentioned "(2) Measurement of the diameter of the first end and the diameter of the second end", the shape of the through hole was evaluated as follows.
[0194] A: The value of (diameter of first end÷diameter of second end)×100 (%) is 80% or more, and a small diameter portion of 65% or more and less than 100% of the diameter of the second end exists between the first end and the second end.
[0195] B: The value of (diameter of first end ÷ diameter of second end)×100 (%) is 75% or more and less than 80%, and a small diameter portion of 65% or more and less than 100% of the diameter of the second end exists between the first end and the second end.
[0196] C: The value of (diameter of first end ÷ diameter of second end)×100 (%) is 65% or more and less than 75%, and there is a small diameter portion between the first end and the second end that is 65% or more and less than 100% of the diameter of the second end.
[0197] The value of D: (diameter of the first end÷diameter of the second end)×100(%) is less than 65%, and a small diameter portion exists between the first end and the second end.
[0198] E: There is no small diameter portion.
[0199] The results of the above evaluation tests are shown in Tables 2 and 3 below.
[0200] 4. Evaluation of printed wiring boards
[0201] (1) Preparation of test pieces
[0202] The film formation method and film thickness during film preparation, the diameter of the circular pattern during exposure, the wavelength and cumulative light amount of ultraviolet rays, and the spraying time of the alkaline aqueous solution during development were set as shown in Tables 4 to 6. In addition, the test piece was prepared by the method described in "(1) Preparation of test piece" in the above "1. Evaluation of composition". It should be noted that when a plurality of numerical values are described in the wavelength column, ultraviolet rays having wavelengths of each numerical value are irradiated simultaneously.
[0203] The test pieces were evaluated as follows. In Comparative Example 1, development was not possible and no evaluation was performed. In Comparative Example 3, peeling of the film due to insufficient curing was observed at a certain location during development and no evaluation was performed.
[0204] (2) Determination of the diameter of the first end and the diameter of the second end
[0205] The specimen was cut in two on a plane parallel to the axis of the through hole, and the cross section was observed using an electron microscope (SEM). Based on the image thus obtained, the diameter of the first end and the diameter of the second end of the through hole were measured. In addition, the value of (diameter of the first end ÷ diameter of the second end) × 100 (%) was calculated.
[0206] (3) Whether there is a small diameter section
[0207] Based on the image obtained in the above “(2) Measurement of the diameter of the first end and the diameter of the second end”, it was confirmed whether there was a small diameter portion between the first end and the second end of the through hole, and the evaluation was performed as follows.
[0208] A: There is a small-diameter portion between the first end and the second end, and the minimum diameter of the small-diameter portion is 65% or more and less than 100% of the diameter of the second end.
[0209] B: There is a small diameter portion between the first end and the second end, and the minimum diameter of the small diameter portion is less than 65% of the diameter of the second end.
[0210] C: There is no small diameter portion between the first end and the second end.
[0211] (4) Path shape evaluation
[0212] Based on the images obtained in the above-mentioned "(2) Measurement of the diameter of the first end and the diameter of the second end", the shape of the through hole was evaluated as follows.
[0213] A: The value of (diameter of first end÷diameter of second end)×100 (%) is 80% or more, and a small diameter portion of 65% or more and less than 100% of the diameter of the second end exists between the first end and the second end.
[0214] B: The value of (diameter of first end ÷ diameter of second end)×100 (%) is 75% or more and less than 80%, and a small diameter portion of 65% or more and less than 100% of the diameter of the second end exists between the first end and the second end.
[0215] C: The value of (diameter of first end ÷ diameter of second end)×100 (%) is 65% or more and less than 75%, and there is a small diameter portion between the first end and the second end that is 65% or more and less than 100% of the diameter of the second end.
[0216] The value of D: (diameter of the first end÷diameter of the second end)×100(%) is less than 65%, and a small diameter portion exists between the first end and the second end.
[0217] E: There is no small diameter portion.
[0218] (5) Path connection reliability
[0219] For the test piece, the outer surface of the interlayer insulating layer was roughened by the general desmear treatment described below as a pre-process of the plating treatment.
[0220] The interlayer insulating layer was swelled at 70°C for 10 minutes using a swelling solution for desmearing (Swelling Dip Securiganth P manufactured by Atotech Japan Co., Ltd.), so that the surface of the interlayer insulating layer swelled, and then the interlayer insulating layer was washed with hot water. Next, the surface of the interlayer insulating layer was treated at 70°C for 10 minutes using a desmearing solution (an oxidant containing potassium permanganate. Concentrate Compact CP manufactured by Atotech Japan Co., Ltd.), so that it was roughened, and then the interlayer insulating layer was washed with hot water. Next, the surface of the interlayer insulating layer was treated at 40°C for 5 minutes using a neutralizing solution (Reduction solution Securiganth P manufactured by Atotech Japan Co., Ltd.), so that the residue was removed, and then the interlayer insulating layer was washed with water.
[0221] Next, an electroless copper plating process was performed on the interlayer insulating layer to produce an initial conductor, and then heated at 150° C. for 1 hour. 2 Under the conditions of , electrolytic copper plating was performed on the initial conductor, and then heated at 180° C. for 30 minutes. Thus, a first conductor layer with a thickness of 33 μm was formed on the interlayer insulating layer, and a via conductor was formed in the through hole.
[0222] Next, the test piece was subjected to a temperature cycle test of 500 cycles, in which the test piece was exposed to -55°C for 15 minutes and then to 125°C for 15 minutes. The resistance value between the first conductor layer and the second conductor layer through the via conductor was measured before and after the test, and the change rate was evaluated as follows.
[0223] A: The change rate of the resistance value before and after the temperature cycle test is less than 8%.
[0224] B: The rate of change in resistance value before and after the temperature cycle test is 8% or more and less than 10%.
[0225] C: The rate of change in resistance value before and after the temperature cycle test is 10% or more.
[0226] The results of the above evaluation tests are shown in Tables 4 to 6 below.
[0227] [Table 1]
[0228]
[0229] [Table 2]
[0230]
[0231] [Table 3]
[0232]
[0233] [Table 4]
[0234]
[0235] [Table 5]
[0236]
[0237] [Table 6]
[0238]
Claims
1. A method for manufacturing a printed wiring board, The printed wiring board comprises a first conductor layer, an insulating layer, a second conductor layer overlapping the insulating layer, an interlayer insulating layer interposed between the first conductor layer and the second conductor layer, a through hole penetrating the interlayer insulating layer, and a via conductor arranged in the through hole and electrically connecting the first conductor layer and the second conductor layer. The interlayer insulating layer is a cured product of a negative photosensitive resin composition containing a carboxyl resin A, an unsaturated compound B having at least one ethylenically unsaturated bond in one molecule, and a photopolymerization initiator C. The through hole has a first end, a second end, and a small diameter portion, the first end being an end on the first conductor layer side, the second end being an end on the second conductor layer side, the small diameter portion being located between the first end and the second end and having a diameter smaller than that of the second end, The diameter of the first end is 65% to 90% of the diameter of the second end. The minimum diameter of the small diameter portion is 65% to 90% of the diameter of the second end. The method comprises: A negative photosensitive resin composition and a substrate are prepared, wherein the negative photosensitive resin composition contains the carboxyl-containing resin A, the unsaturated compound B having at least one ethylenically unsaturated bond in one molecule, and the photopolymerization initiator C, and the substrate has an insulating layer and the second conductive layer overlapping the insulating layer. A film made of the photosensitive resin composition is superimposed on the substrate so as to cover the second conductive layer. After exposing a negative pattern region of the film including the through hole pattern, developing the region using an alkaline aqueous solution, the interlayer insulating layer and the through hole penetrating the interlayer insulating layer are formed; When the film is exposed, the film is irradiated with light having spectral intensity at at least one wavelength in a wavelength region of 365 nm±65 nm and having no spectral intensity at a wavelength of 435 nm or more.
2. The method for manufacturing a printed wiring board according to claim 1, wherein: The method comprises overlapping a dry film made of the photosensitive resin composition on the substrate to form the film.
3. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The diameter of the first end is 100 μm or less.
4. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The carboxyl group-containing resin A contains a carboxyl group-containing resin A1 having a bisphenol fluorene skeleton.
5. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The weight average molecular weight of the carboxyl-containing resin A is 700 to 100,000.
6. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The carboxyl group-containing resin A contains a component having an acid value of 65 mgKOH / g to 150 mgKOH / g.
7. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The percentage of the unsaturated compound B relative to the carboxyl group-containing resin A is 5 mass % to 45 mass %.
8. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The percentage of the photopolymerization initiator C relative to the carboxyl group-containing resin A is 1 mass % to 30 mass %.
9. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The photopolymerization initiator C contains at least one selected from the group consisting of an acylphosphine oxide-based photopolymerization initiator, an α-aminoalkylphenone-based photopolymerization initiator, and an oxime ester-based photopolymerization initiator.
10. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The photosensitive resin composition further contains an epoxy resin D.
11. The method for manufacturing a printed wiring board according to claim 10, wherein: The equivalent of the epoxy group of the epoxy resin D is 0.1 to 5 with respect to 1 equivalent of the carboxyl group of the carboxyl group-containing resin A.
12. The method for manufacturing a printed wiring board according to claim 1 or 2, wherein: The photosensitive resin composition further contains an organic filler (E).
13. The method for manufacturing a printed wiring board according to claim 12, wherein: The organic filler E has a reactive group.
14. The method for manufacturing a printed wiring board according to claim 13, wherein: The reactive group includes at least one group selected from the group consisting of a carboxyl group, an amino group, an epoxy group, a vinyl group, and a hydroxyl group.
15. The method for manufacturing a printed wiring board according to claim 12, wherein: The ratio of the organic filler E to the carboxyl group-containing resin A is 1% by mass to 100% by mass.
Citation Information
Patent Citations
Method for manufacturing multilayer printed wiring board
JP2016181731A
Printed wiring board and method for manufacturing the same
CN101925266A
Circuit board and process for producing same
CN105323960A
Method for producing multilayer printed wiring board, and multilayer printed wiring board
CN110999554A